Piezoelectricity across 2D Phase Boundaries. Issue 39 (24th August 2022) - Puthirath, Anand B.; Zhang, Xiang; Krishnamoorthy, Aravind; Xu, Rui; Samghabadi, Farnaz Safi; Moore, David C.; Lai, Jiawei; Zhang, Tianyi; Sanchez, David E.; Zhang, Fu; Glavin, Nicholas R.; Litvinov, Dmitri; et al.
Abstract: Piezoelectricity in low‐dimensional materials and metal–semiconductor junctions has attracted recent attention. Herein, a 2D in‐plane metal–semiconductor junction made of multilayer 2H and 1T′ phases of molybdenum(IV) telluride (MoTe2 ) is investigated. Strong piezoelectric response is observed using piezoresponse force microscopy at the 2H–1T′ junction, despite that the multilayers of each individual phase are weakly piezoelectric. The experimental results and density functional theory calculations suggest that the amplified piezoelectric response observed at the junction is due to the charge transfer across the semiconducting and metallic junctions resulting in the formation of dipoles and excess charge density, allowing the engineering of piezoelectric response in atomically thin materials. Abstract : The piezoelectric responses at 2D‐material phase boundaries are studied and a strong piezoelectric response at the 2H–1T′ junction is observed, owing to the charge transfer across the semiconducting and metallic junctions, resulting in the formation of dipoles and excess charge density, allowing the engineering of piezoelectric response in atomically thin materials.